Vector Control of Multimotor Drive and Introduction to Single Multiphase Motor - Nanoty, Archana S.; Chudasama, A. R. (Research and Developments in Engineering Research Vol. 4, 2023)
Three-phase induction machines are currently the industry standard for industrial electrical drives. These machines are replacing dc drive systems for a variety of reasons, including cost, dependability, robustness, and maintenance-free operation. Three phase induction motors are operated as separately stimulated dc motors for field-oriented control. The advancement of power electronics and signal processing systems has eliminated one of the most significant drawbacks of such ac systems: the issue of control. The task of variable speed control of induction devices is no longer a disadvantage with modern field oriented vector control systems. The desire to improve system performance, particularly when power supply and semiconductor power ratings are limited, promotes the usage of phase numbers other than three. In this chapter a novel scheme of connecting two, three phase induction motors in parallel fed by two inverters; viz. VSI and CSI and their vector control is presented and instead of using two inverters for three phase motor, a single multiphase motor design is discussed.